FABLE Scenathon 2023: Pathways for food and land-use systems in India - Saha, Ankit; Singh, Vartika; Das, Prantika; Joshi, Aditi; Jha, Chandan Kumar; Ghosh, Ranjan Kumar; Stevanović, Miodrag; Lotze-Campen, Hermann (Sustainable Development Solutions Network, 2024)
Our food and land-use systems are critical for staying within our planetary boundaries and the Earth’s system resilience. Among the six Transformations required to achieve the Sustainable Development Goals (SDGs), the fourth Transformation—focusing on food, land, and water—is crucial. This Transformation is key to achieving SDG 2 (Zero Hunger), SDG 6 (Clean Water and Sanitation), SDG 12 (Responsible Consumption and Production), SDG 13 (Climate Action), SDG 14 (Life Below Water), and SDG 15 (Life on Land). Moreover, it significantly supports the remaining SDGs, underscoring its crucial role in fostering a sustainable future.